Mempengaruhi Minat Beli: Analisis e-WOM dan Celebrity Endorsement dengan Citra Merek sebagai Mediasi pada Pengguna Smartphone Transsion di Jabodetabek - Fathurohman, Muhamad; Febrilia, Ika; Krissanya, Nofriska (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The purpose of this research is to determine the positive and significant influence of Electronic Word of Mouth and Celebrity Endorsement on Purchase Intention among Transsion smartphone users in the Jabodetabek area, with Brand Image serving as a mediating variable. Data were collected through a Google Form questionnaire using a 5-point Likert scale. The research1 sample consisted of 200 respondents interested in Transsion smartphones. Data analysis included validity and reliability tests, as well as hypothesis testing using AMOS version 24 software. The results indicated that e-WOM and celebrity endorsement have a positive and significant influence on brand image. Furthermore, e-WOM and brand image significantly impact purchase intention, while celebrity endorsement does not have a direct significant effect on purchase intention. Brand image was found to be a significant mediator between e-WOM and celebrity endorsement with purchase intention.